SAE Technical Paper Series 2001
DOI: 10.4271/2001-01-1692
|View full text |Cite
|
Sign up to set email alerts
|

Design and Transient Simulation of Vehicle Air Conditioning Systems

Abstract: This paper describes the need for dynamic (transient) simulation of automotive air conditioning systems, the reasons why such simulations are challenging, and the applicability of a general purpose off-the-shelf thermohydraulic analyzer to answer such challenges. An overview of modeling methods for the basic components are presented, along with relevant approximations and their effect on speed and accuracy of the results. THE MOTIVATION: THE NEED FOR DYNAMIC MODELING Major Department of Energy (DoE) objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…hardware-in-the-loop/ software-in-the-loop simulation, embedded system emulators) require that the code run in real-time. While finite volume or finite difference models are fully capable of predicting system transients (Cullimore and Hendricks, 2001;MacArthur and Grald, 1989;Eborn et al, 2005;Limperich et al, 2005), Grald and MacArthur (1992) showed that the ''lumped parameter'' or ''moving-boundary'' method is much faster. Even though real-time capability using a finite volume technique has been demonstrated by Rossi and Braun (1999), the faster speed of the moving-boundary method has caused it to become the method of choice for controls' purposes (Rasmussen, 2006;Willatzen et al, 1998;He et al, 1995;Leducq et al, 2003;Cheng and Asada, 2006;Jensen and Tummescheit, 2002) The primary reason for the speed difference is that the moving-boundary method divides the heat exchanger into a minimum number of zones (at most three), representing regions where refrigerant is in the superheated vapor, saturated mixture, and sub-cooled liquid phases.…”
Section: Introductionmentioning
confidence: 97%
“…hardware-in-the-loop/ software-in-the-loop simulation, embedded system emulators) require that the code run in real-time. While finite volume or finite difference models are fully capable of predicting system transients (Cullimore and Hendricks, 2001;MacArthur and Grald, 1989;Eborn et al, 2005;Limperich et al, 2005), Grald and MacArthur (1992) showed that the ''lumped parameter'' or ''moving-boundary'' method is much faster. Even though real-time capability using a finite volume technique has been demonstrated by Rossi and Braun (1999), the faster speed of the moving-boundary method has caused it to become the method of choice for controls' purposes (Rasmussen, 2006;Willatzen et al, 1998;He et al, 1995;Leducq et al, 2003;Cheng and Asada, 2006;Jensen and Tummescheit, 2002) The primary reason for the speed difference is that the moving-boundary method divides the heat exchanger into a minimum number of zones (at most three), representing regions where refrigerant is in the superheated vapor, saturated mixture, and sub-cooled liquid phases.…”
Section: Introductionmentioning
confidence: 97%
“…Some examples of previously developed non-commercial full system-level simulation include [6,7,8]. However, to the best of our knowledge, none of them is both developed in the widely used dynamic system simulation platform MATLAB/ Simulink (which is helpful for controls engineers) and available to the public at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…SINDA/FLUINT is a comprehensive software package used by over 400 sites in the aerospace, energy, electronics, automotive, aircraft, HVAC, and petrochemical industries for design, simulation, and optimization of systems involving heat transfer and fluid flow. It is the NASA-standard analyzer for thermal control systems (Baumann et al 2000;Cullimore et al 2004a, b, Cullimore 2001Cullimore and Hendricks 2001;Hendricks 2001;Panczak et al 1998).…”
Section: Ttcs Dynamic Modelmentioning
confidence: 99%